Novel saccharin analogs as promising antibacterial and anticancer agents: synthesis, DFT, POM analysis, molecular docking, molecular dynamic simulations, and cell-based assay - Abdellattif, Magda H.; Elkamhawy, Ahmed; Hagar, Mohamed; Hadda, Taibi Ben; Shehab, Wesam S.; Mansy, Wael; Belal, Amany; Arief, M. M. H.; Hussien, Mostafa A. (Frontiers in Pharmacology, 2022)
Saccharine is classified as a pharmacologically significant active scaffold for various biological activities, including antibacterial and anticancer. Herein, saccharinyl hydrazide (1) was synthesized and converted into 2-[(2Z)-2-(1,1-dioxo-1,2-dihydro-3H-1λ6,2- benzothiazole-3-ylidene) hydrazinyl] acetohydrazide (5), which was employed as a key precursor for synthesizing a novel series of small molecules bearing different moieties of monosaccharides, aldehydes, and anhydrides. Potent biological activities were found against Staphylococcus and Escherichia coli, and the results obtained indicated that compounds 6c and 10a were the most active analogs with an inhibition zone diameter of 30–35 mm. In cell-based anticancer assay over Ovcar-3 and M-14 cell lines, compound 10a was the most potent analog with IC50 values of 7.64 ± 0.01 and 8.66 ± 0.01 µM, respectively. POM (Petra Orisis Molinspiration) theoretical method was used to calculate the drug score of tested compounds and compare them with their experimental screening data. Theoretical DFT calculations were carried out in a gas phase in a set of B3LYP 6-311G (d,p). Molecular docking studies utilizing the MOE indicated the best binding mode with the highest energy interaction within the binding sites. The MD performed about 2ns simulations to validate selected compounds' theoretical studies.